ANALISIS KESULITAN BELAJAR SISWA KELAS V PADA MATERI OPERASI HITUNG PERKALIAN SERTA UPAYA GURU DALAM MENGATASINYA DI SD NEGERI 129II BABEKO - Zaharatud Diniah; Tri Wera Agrita; Antok Kurniawan (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2026)
This study aims to describe the form of learning difficulties of fifth grade students in the material of multiplication arithmetic operations, identify the factors causing them, and explain the efforts of teachers in overcoming these difficulties. The study used a descriptive qualitative approach with subjects of 5 students and 1 teacher of fifth grade of Elementary School 129/II Babeko. Data were collected through observation, interviews, and documentation. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation and drawing conclusions. The results of the study showed that (1) the forms of student learning difficulties include difficulty memorizing basic multiplication facts, understanding multiplication concepts, performing simple calculations, solving compound multiplication, and being less careful in calculating. (2) The factors causing learning difficulties come from internal factors in the form of low conceptual understanding and mastery of basic multiplication facts, as well as external factors in the form of lack of practice, learning support at home and the use of limited learning media. (3) Teachers' efforts in overcoming these difficulties are carried out through the use of concrete media, providing repeated practice, remedial learning, individual guidance, and learning motivation. Thus, students' learning difficulties in the material of multiplication arithmetic operations require appropriate handling so that students' understanding of mathematical concepts can improve. The results of this study are expected to be a consideration for teachers in designing more effective learning strategies to improve the multiplication skills of elementary school students.